Real-Time Process Monitoring Platform: Technical Implementation - Batyuk, Anatoliy; Voityshyn, Volodymyr (Видавництво Львівської політехніки, 2018)
Modern IT systems produce vast amount of event data that contains digital footprints of processes automated by means of software. Mining of process models from real-life data brings a lot of benefits since it reveals an actual situation with further possibilities of its analysis and improvements. Technical implementation of a real-time process monitoring platform is represented. The platform is based on the lambda architecture pattern and incorporate an adoption of a streaming process discovery algorithm.
Keywords: process mining; streaming process discovery; event data; lambda architecture